Peran Pendidikan Pancasila dan Kewarganegaraan dalam menghadapi arus globalisasi - Triswantono, Dhanie Raihan; Antari, Ervin Dwi (Journal of Contemporary Issues in Primary Education, 2023)
The increasingly rapid flow of globalization today, of course, has a major negative impact on the civic character of the Indonesian population, especially young people. Therefore, it is not surprising that the character of the Indonesian nation based on Pancasila is now starting to fade. Therefore, this research examines the role of Pancasila and Citizenship Education in facing the flow of globalization. This research uses quantitative methods obtained from literature studies and scientific data that correspond to facts, then presented in writing. The results of this literature study show that the role of Pancasila and Citizenship lessons in the rapid wave of globalization, is that it really has an impact on young people in securing and practicing the existing PPKN morals and creating young people who are still in school and then adhere to the guidelines, are moral, obedient, commitment to obeying applicable rules, sharp thinking as well as high levels of worship and creativity.